Ecological effects of water and fertilizer addition on poplar-planting soil - Yimin You; Shitong Li; Xiao Li; Liran Wang; Hongxing Wang; Luping Jiang; Yanhui Peng; Zhongyi Pang; Xiyang Zhao (mSystems)
ABSTRACT While irrigation and fertilization are basic cultivation practices in poplar plantations on a global scale, the impact of these practices on the environment is not well understood. Here, we demonstrate that water-urea addition and water-compound fertilizer addition differentially impact soil ecosystems. We report that water-fertilizer addition did not significantly alter taxonomic diversity indices, but it did drive significant shifts in microbial community composition, reflected by changes in the relative abundance of specific taxa and their functional profiles. Water-urea addition reduced Proteobacteria and Actinobacteria in non-rhizosphere soils while increasing Acidobacteria and Chloroflexi. In contrast, water-compound fertilizer additions increased Proteobacteria and Actinobacteria dominance in rhizosphere soils. Water-fertilizer addition changed microbial composition and functional gene abundance linked to nitrogen and sulfur cycling. Water-urea treatment enriched denitrification genes and dissimilatory nitrate reduction genes (napABC) in rhizosphere soil, while water-compound fertilizer treatment enhanced nitrification (amoABC, HAO) and denitrification gene abundance in both soils. For sulfur (S) cycling, water-urea treatment favored thiosulfate oxidation genes, whereas water-compound fertilizer treatment increased assimilatory sulfate reduction genes. Multi-omics integration linked these microbial dynamics to metabolic reshaping—water-urea increased lipid and secondary metabolites in rhizosphere soils, while water-compound fertilizer additions elevated amino acid-associated metabolites in non-rhizosphere soils. Crucially, water-compound fertilizer addition reduced the gene abundance for the conversion of N2O to N2 (nosZ) and altered sulfur partitioning, whereas water-urea addition elevated soil NO3− and NH4+ but depleted available K. These results highlight trade-offs between nutrient management and microbial-mediated environmental potential, guiding optimized irrigation-fertilizer strategies for sustainable poplar silviculture.IMPORTANCECombined irrigation and fertilizer application affect microbial community composition, and soil nitrogen and sulfur cycles (by regulating microbial composition and the abundance of genes related to nitrogen and sulfur cycles). Water-urea reduced Proteobacteria, increased Acidobacteria, and enriched denitrification genes, elevating soil NO3−/NH4+. Water-compound fertilizer boosted Proteobacteria and nitrification genes. Water-urea increased rhizosphere lipids/secondary metabolites; compound fertilizer elevated non-rhizosphere amino acids. These trade-offs between nutrient gains and environmental risks guide optimized poplar plantation management.